PEDAGOGICAL APPROACHES OF ALIKHONTORA SOGUNI IN DEVELOPING THE MORAL QUALITIES OF TEENAGE STUDENTS (Multidisciplinary Journal of Science and Technology, 2024)
In this article, the pedagogical views of Alikhontora Soguni on the development of moral qualities of adolescent students are described, as well as relevant conclusions are drawn on this topic.